2001
DOI: 10.1037/0096-1523.27.6.1287
|View full text |Cite
|
Sign up to set email alerts
|

New objects dominate luminance transients in setting attentional priority.

Abstract: Both the sudden appearance of an object and sudden changes in existing object features influence priority in visual search. However, direct comparisons of these influences have not been made under controlled conditions. In 5 visual search experiments, new object onsets were compared directly with changes in the luminance of old objects. Factors included the luminance contrast of items against the background, the magnitude of luminance change, and the probability that these changes were associated with the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 58 publications
7
109
1
Order By: Relevance
“…At the same time, the presence of an abrupt onset in the target display interfered with responding, whether the red cue was valid or invalid. Consistent with earlier claims suggesting that onsets capture attention in a stimulus-driven manner (Belopolsky, Theeuwes, & Kramer, 2005;Christ & Abrams, 2008;Enns, Austen, Di Lollo, Rauschenberger, & Yantis, 2001;Gellatly, 1999;Remington, Johnston, & Yantis, 1986;Theeuwes, 1990Theeuwes, , 1994Yantis & Jonides, 1984), Schreij et al concluded that even when observers adopt a clear top-down set for color, they cannot prevent attentional capture by the onset. According to the contingent capture hypothesis, the presence of the onset should have had no effect on responding, because it was completely irrelevant to the task.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…At the same time, the presence of an abrupt onset in the target display interfered with responding, whether the red cue was valid or invalid. Consistent with earlier claims suggesting that onsets capture attention in a stimulus-driven manner (Belopolsky, Theeuwes, & Kramer, 2005;Christ & Abrams, 2008;Enns, Austen, Di Lollo, Rauschenberger, & Yantis, 2001;Gellatly, 1999;Remington, Johnston, & Yantis, 1986;Theeuwes, 1990Theeuwes, , 1994Yantis & Jonides, 1984), Schreij et al concluded that even when observers adopt a clear top-down set for color, they cannot prevent attentional capture by the onset. According to the contingent capture hypothesis, the presence of the onset should have had no effect on responding, because it was completely irrelevant to the task.…”
supporting
confidence: 75%
“…Related to the idea that the onset has to be sufficiently salient, previous research has shown that the capturing power of an onset is largest when it also makes up a new perceptual object (Enns et al, 2001;Yantis & Hillstrom, 1994). The onset of a complete box including a letter, as used by us here, can be regarded as a new object, but this may not be true for the four small white dots that Folk et al (1992) used as their onset precue.…”
Section: Additivitymentioning
confidence: 87%
“…This pattern has been found in particular if the object is relevant for the task (Yantis and Egeth 1999), but even persists if attending to the object that pops-out is known to be irrelevant and disadvantageous to the performance of the task (e.g., Pashler 1988;Theeuwes 1991Theeuwes , 1992. Especially, unique colors (e.g., Nagy and Winterbottom 2000;Galfano 2000, 2001;Turatto et al 2004) and luminance contrasts (Enns et al 2001) seem very effective at capturing attention.…”
Section: Theoretical Accounts Of the Effect Of Cueing On Perceptual Amentioning
confidence: 97%
“…Recently, Enns et al (2001) reported a related finding: An item featuring a maximum luminance change (i.e., a polarity reversal: changing from black to white on a gray background) did not get as much priority in search as an item that newly appeared in an empty location (i.e., whose luminance changed from the gray background to either black or white). Enns et al concluded, as we do here, that the visual system is biased toward new object appearances rather than luminance changes.…”
Section: Attentional Capturementioning
confidence: 99%